The Changing Role of Ministers in the Legislative Agenda in Brazil - Rennó, Lúcio; Wojcik, Stefan (Revista Ibero-Americana de Estudos Legislativos, 2015)
Who, within the Cabinet, participates in elaborating the government’s legislative agenda, and why? How has the role of ministers in elaborating the legislative agenda changed over time? In this paper, we discuss the structure of legislative bill cosponsorship networks among cabinet members in Brazil. Are ministers serious participants in the elaboration of the agenda, sharing its authorship with colleagues from their and other parties in the coalition? We develop a theory of cabinet members’ participation in the formulation of the government’s legislative agenda in the Brazilian Congress. Using descriptive statistics and network-analytic techniques, we reveal continuity and change in the role of ministers in the legislative agenda over time.